Pengenalan Literasi Branding bagi Usaha Kuliner di Krobokan Semarang Barat - Universari, Nuria; Prapti, Rr. Lulus; M. Paramitayana, Haris (TEMATIK, 2024)
The Village of Krobokan in the Semarang Barat Sub-District is renowned for producing Semarang’s distinctive culinary offerings. However, Micro Small, and Medium Enterprises (MSMEs) in Krobokan Village are confronted with various challenges, including a deficiency in branding capabilities. The primary objective of this community dedication program is to increase the knowledge of culinary business owners in Krobokan Village about branding to implement branding strategies to make their products known to the wider community. A proper understanding of branding will help MSMEs develop their businesses and increase sales, despite having limited budgets and resources. The method used to provide branding literacy education is through lectures. The results of the community dedication program show a positive change in culinary business owners who participated, as they gained an understanding of branding, personal branding, and the benefits of business development.
Keywords: Branding; Culinary; MSMEs